2016
DOI: 10.1021/acs.energyfuels.6b01576
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mechanism of Coal after Cryogenic Freezing with Cyclic Liquid Nitrogen and Its Influences on Coalbed Methane Exploitation

Abstract: This study explores how liquid nitrogen (LN2) freezing affects the physical pore and fracture structure of coal. Under lab-controlled conditions, coal specimens were frozen with LN2 under different conditions and thawed, and then the uniaxial compressive strengths, acoustic emissions, and ultrasonic wave velocities of the different specimens were compared. After 60 min of freezing for one set of specimens and 30 freeze–thaw cycles for another set, the elastic moduli of the coal specimens decreased by 47.8% for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Passive measurements involve the analysis of acoustic emissions in samples under the influence of mechanical or thermal test impacts. The most common method involves the cyclic F-T of coal samples and their subsequent uniaxial loading up to failure together with the registration of acoustic emission parameters (Qin et al 2016(Qin et al , 2018. Other physical effects are sometimes used instead of uniaxial loading, such as rapid heating of a sample with simultaneous acoustic emission registration (Novikov et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Passive measurements involve the analysis of acoustic emissions in samples under the influence of mechanical or thermal test impacts. The most common method involves the cyclic F-T of coal samples and their subsequent uniaxial loading up to failure together with the registration of acoustic emission parameters (Qin et al 2016(Qin et al , 2018. Other physical effects are sometimes used instead of uniaxial loading, such as rapid heating of a sample with simultaneous acoustic emission registration (Novikov et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, CBM is very difficult to be drained without external disturbances because methane molecules can tightly adsorb on the micro-pore surface. Over the past decade, many studies have focused on waterless thermal-shock fracturing techniques [3][4][5], because hydraulic fracturing technology consumes a large volumes of water and may affect public health and the environment [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the coal permeability increased by 48.89%-93.55% after LN 2 cooling treatment, and the compressive strength of cool-treated coal specimens decreased by 16.18%-33.74% compared with intact specimens [4]. Under laboratory conditions, Qin et al [5,10] studied the effect of LN 2 freezing on pores and fracture structures in coal. After LN 2 freezing-thaw cycles, they found that the coal specimens' elastic moduli, uniaxial compressive strengths (UCSs) and longitudinal wave velocities dropped while the porosities and Poisson's ratios increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo [15] investigated the laws of the crack growth and permeability evolution of coal under the LN 2 freezing. Qin et al [16] investigated the effects of LN 2 freezing on mechanical and physical properties of coal. The results showed that LN 2 freezing has an obvious weakening effect on the wave velocity and compressive strength of coal.…”
Section: Introductionmentioning
confidence: 99%